Influencing factors and mechanism of tourists’ pro-environmental behavior – Empirical analysis of the CAC-MOA integration model - Tang, Haiyan; Ma, Yong; Ren, Jie (Frontiers in Psychology, 2022)
Tourism has been perceived as an environmentally friendly industry for a long term, but the negative impact of tourist irresponsible behavior on the environment cannot be ignored. Tourists’ pro-environmental behavior is crucial to the destination’s sustainable development. Taking stimulus-organism-response theory as a framework, this study explores the factors and mechanisms influencing tourists’ pro-environmental behaviors by integrating cognitive-affective-conative (CAC) theory and motivation-opportunity-ability (MOA) theory. Through the PLS-SEM analysis with 548 questionnaires, the driving mechanism of tourists’ pro-environmental behavior was deeply explored. The results indicate that tourists’ environmental knowledge, participation motivation, and opportunity have significant positive effects on pro-environmental behavior, but the role of participation ability on tourists’ pro-environmental behavior is not confirmed. Tourists have significant environmental self-identity and environmental commitment, and these affections actively promote tourists’ pro-environmental behavior. Except for the participation ability, the other three factors, respectively, influence tourists’ environmental behavior through the mediating effects of environmental self-identity and environmental commitment. Given the limited literature integrating CAC and MOA theories within research on tourists’ pro-environmental behavior, these findings provide new perspectives for future research. This research enriches the literature on the factors influencing tourist pro-environmental behavior and also provides practical guidance for promoting tourists’ pro-environmental behavior.